Ambulatory Cardiovascular Monitoring Via a Machine‐Learning‐Assisted Textile Triboelectric Sensor (Adv. Mater. 41/2021). Issue 41 (12th October 2021) - Fang, Yunsheng; Zou, Yongjiu; Xu, Jing; Chen, Guorui; Zhou, Yihao; Deng, Weili; Zhao, Xun; Roustaei, Mehrdad; Hsiai, Tzung K.; Chen, Jun
Abstract : Personalized Healthcare In article number 2104178, Jun Chen and co‐workers report a waterproof textile‐based wearable cardiovascular monitoring system that is developed via integration of a triboelectric sensor, a signal‐processing circuit, a Bluetooth module, and a customized user‐friendly app interface. With the assistance of machine‐learning algorithms, this system can perform continuous blood‐pressure monitoring against body motion and perspiration.